(untitled) (Actualizaciones en Sida e Infectología, 2023)
INTRODUCTION Perinatal infections can be transmitted to the fetus and newborn. Syphilis, HIV and Hepatitis B must be screened during pregnancy. OBJECTIVE To know incidence, prevalence and management of syphilis, HIV and hepatitis B in the mother/child pairing. Compare results with official statistics. MATERIALS AND METHODS Retrospective, descriptive and analytical study, through review of medical records from the Sanatorio la Cañada and Hospital Pasteur in Villa Maria, Cordoba. Period 12/01/2020 to 03/31/2021. RESULTS 870 pregnancies studied, 5.3% reactive syphilis serology and 1% HIV. Maternal syphilis incidence 52.87 per 1000 pregnancies, percentage of positivity 5.3%. 76.1% under 30 years old. 41% late diagnoses. 37% incomplete treatments. Congenital syphilis incidence 18.3 per 1000 live newborns. Percentage of maternal HIV posivity 0.68%. 66.7% under 30 years old. 100% underwent correct treatment and 77.7% undetectable viral load at delivery. 100% exposed newborns studied, all undetectable viral load at birth. No cases of Hepatitis B. CONCLUSION 6.3% of pregnant women presented at least one reactive serology, prevailing age under 30 years. Percentage of maternal syphilis posivity lower than published by province of Cordoba. Congenital syphilis incidence exceeded the provincial and national (18.3 vs 1.18 vs 1.14). Percentage of maternal HIV posivity exceeded provincial ones. No detected vertical transmission of HIV at birth. Hepatitis B prevalence lower than official data. Pregnant women diagnosed with HIV have more follow-up from the health system than those diagnosed with syphilis.